Management of Coffee Leaf Rust Disease in India: Evidence for Channels of Communication - M. R. Narayana (Journal of Applied Communications, 2013)
Management of coffee leaf rust (CLR) disease is essential to avoid its resultant production losses of Arabica coffee. Communication channels provide coffee farmers with the required knowledge for management by the recommended disease control methods and their applications. In this context, this paper analyses the role of communication channels for management of CLR by using a newly collected household level data of 575 Arabica coffee farmers in India. Management is focused on cultivation of resistant varieties and application of chemical sprays. Two methods of analyses are developed: Descriptions based on spatially aggregate data. Second, estimations based on Binary Logit Model using individual data. Descriptions show that prevalence of CLR is universal; key channels of communication are fellow farmers, extension workers and television; and desired channels of communications include on-farm demonstration and training workshops. While individual communication is most preferred channel, farmers’ associations are considered useful institutional channels of communication. Estimations distinguish communication channels by fellow farmers and extension workers and show significant differences in nature and extent of impact of these communication channels on CLR management by resistant varieties and chemical sprays. These results have important implications for identifying and improving the current and future information needs and channels of communication for effective management of CLR, especially for small farmers with lower educational attainments in India. However, the approach and implications of this paper are of general relevance and applicability for other coffee growing countries in Asia and Africa.
Keywords: Coffee Arabica; leaf rust; coffee varieties; fungicides; small farmers